Winter 2022 / Hiver 2022 - McGill Community For Lifelong Learning (MCLL) (2022)

Moderators' Handbook - McGill Community For Lifelong Learning (MCLL) (2021)

The Newsletter - McGill Community For Lifelong Learning (MCLL) (2021)
Number of pages: 12

The Newsletter - McGill Community For Lifelong Learning (MCLL) (2021)
issued: Spring, 2021/Summer, 2021 Number of pages: 16

The Newsletter - McGill Community For Lifelong Learning (MCLL) (2021)
Number of pages: 17

Operating Rules - McGill Community For Lifelong Learning (MCLL) (2022)

University-based Approaches for Older Adults : Adapting Universities for the 100-year Lifespan - McGill Community For Lifelong Learning (MCLL) (2020)
This study, University-Based Approaches for Older Adults: Adapting Universities for the 100-year Lifespan, uses the McGill Community for Lifelong Learning (MCLL) as a case study to probe issues related to seniors’ learning within university contexts, including demographics, effects of learning on the lives of older adults, mutual benefits and expectations for learners and the university community of which they are members. The intention of this research is to enable the continuous improvement of MCLL and, given national and international demographic shifts, to add new perspectives to the literature on the increasingly vital topic of continuing to learn throughout the lifespan.

The Newsletter : Fall 2020: Volume 31, No. 2 - McGill Community For Lifelong Learning (MCLL) (2020)
Number of pages: 12

Fall 2022 : MCLL News - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 12

Annual Report : 2020-2021 - McGill Community For Lifelong Learning (MCLL) (2021)

Survey of MCLL Moderator Engagement : Report to the MCLL Council - McGill Community For Lifelong Learning (MCLL) (2021)
In December 2019, Council requested that the Planning Committee create and administer a survey of moderators to inquire about their engagement in the MCLL community in the service of retaining and recruiting moderators. Due to the COVID-19 outbreak and the high-priority burden the pandemic put on various committees, the survey was delayed until late in the Fall 2020 term. This document reports on the survey results and includes, in appendices, the survey questions as well as the detailed results including all comments received by respondents.

November 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 7

October 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 3

September 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 6

McGill Community For Lifelong Learning : Fall 2021 - McGill Community For Lifelong Learning (MCLL) (2021)

Spring 2020 Program / Printemps 2020 Programme - McGill Community For Lifelong Learning (MCLL) (2020)

December 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)
Number of pages: 3

March 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)
Number of pages: 4

June 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)
Number of pages: 3

January 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 3

February 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 4

June 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 6

March 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 4

May 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)
Number of pages: 3

May 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 7

November 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)
Number of pages: 4

October 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)
Number of pages: 3

September 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)
Number of pages: 4

April 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2021)
Number of pages: 5

April 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)
Number of pages: 5

December 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)
Number of pages: 6

February 2024 eBulletin - McGill Community For Lifelong Learning (MCLL) (2024)
Number of pages: 6

November 2023 eBulletin - McGill Community For Lifelong Learning (MCLL) (2023)
Number of pages: 9